The role of electric field, peripheral chains, and magnetic effects on significant 1H upfield shifts of the encapsulated molecules in chalcogen-bonded capsules. Issue 35 (27th August 2021) - Tzeli, Demeter; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula; Rahman, Faiz-Ur; Yu, Yang; Rebek, Julius
Abstract : Significant 1 H upfield chemical shifts of the guests in the capsules are consequences of polarizability of chalcogens, electric field effects and peripheral chains. The effects of the electric field and of magnetic field are of equal importance. Abstract : The chalcogen-bonded homo-cavitand and hetero-cavitand AY +AY′ capsules (Y, Y′ = Se, Te), as well as their encapsulated complexes with one or two guest molecules have been studied theoretically via density functional theory (DFT), while the 1 H NMR spectra of the homo-cavitand encapsulated complexes (in ASe +ASe ) have been measured experimentally. There is excellent agreement between theoretical and experimental spectra. In all cases, we found significant 1 H upfield shifts which are more intense in the ASe +ASe cage compared to the ATe +ATe and ASe +ATe cages. The non-uniform electron distribution which gives rise to an inherent electric field and a non-zero electric dipole moment of the encapsulated complexes, the induced electric field effects, the magnetic anisotropy which is enhanced due to the polarizability of chalcogen atoms, and the peripheral chains, which are responsible for the solubility of the cages, increase the upfield shifts of 1 H of the encapsulated molecules; the peripheral chains lead to an increase of the upfield shifts by up to 1.8 ppm for H of the rim and up to 1.2 ppm for the terminal H in the interior of the cage. Hence, substantial 1 H upfield chemical shifts of the guests in these capsules are consequences of (i) the enhanced aromaticity of the walls of the capsules due to the polarizability of chalcogen atoms, (ii) the induced and inherent electric field effects, and (iii) the peripheral chains.